Jian-Pi-Yi-Shen Formula Regulates Inflammatory Cytokines Production in 5/6 Nephrectomized Rats via Suppression of NF-κB Activation. (17th July 2018) - Lu, Jiandong; Liu, Xinhui; Liao, Yijiao; Wang, Dongcai; Chen, Jianping; Li, Shunmin
Abstract : Jian-Pi-Yi-Shen formula (JPYSF) is a Chinese herbal decoction used for treating chronic kidney disease (CKD) for over 20 years with good efficiency. However, the mechanism lacks solid evidence. In the present study, we tested the hypothesis that JPYSF may retard CKD progression via inhibition of inflammation in 5/6 nephrectomy (5/6 Nx) rat model. The 5/6 Nx rats were randomly divided into 2 groups: 5/6 Nx group and JPYSF group. Sham-operated rats served as control. JPYSF (2.06 g/kg/d) were administrated by gavage to 5/6 Nx rats daily for 6 weeks. Results showed that JPYSF treatment significantly improved kidney function and pathological injury in 5/6 Nx rats. Multiplex analysis of cytokines revealed that JPYSF reduced proinflammatory cytokines and increased anti-inflammatory cytokine production. Furthermore, JPYSF inhibited the activation of nuclear factor-kappa B (NF- κ B) signaling pathway. In conclusion, our data demonstrated that JPYSF remarkably retards development and progression of CKD in a 5/6 Nx rat model, which may be associated with inhibition of inflammation via NF- κ B signaling pathway.